Increase serum leptin level in Helicobacter pylori infection in Iraqi gastritis patients - ’a Khudhur, Sana; Jameel; Karhoot, Jasim; AL-Khafaji, Jasim; Mohsin, Jasim (AL-Kindy College Medical Journal, 2011)
Background: H.pylori colonized gastric mucosal epithelium will virtually develop gastritis and had the capacity to persist for decades. Pathogenesis is dependent upon strain, virulence host genetic susceptibility, and environmental cofactors. Leptin is a member of the class 1 cytokine family so altered leptin production during ifnect and inflammation that leptin part of the cytokine cascade ,which orchestrates the defense mechanism. Objective: Examin the effect of H.pylori infection on serum leptin level. Methods: One hundred and thirty(130) Patients attending the Endoscopic Unit at "Gastroenterology and Hepatology Teaching Hospital/ Baghdad Medical City"were included in this study with ages range from 18 years to 65 years are the source of specimens to undergo oesophageal gastroduodenoscopy (OGD) compared with twenty healthy control the study began from April 2009 to the end of March 2010 were eligible for this study.Tow types of samples were taken, biopsy for rapid urease test and histopathological examination to detect H.pylori and blood sample for estimation of serum leptin by ELISA test. Results: The results show significant increase in serum leptin concentration(P<0.001)in gastritis patients caused by H.pylori compared with patients control and healthy control. Conclusion: Increase of serum leptin concentration explained the role of leptin in the immune response to H.pylori infection that leptin consider as member of cytokine